Analisis tingkat efektivitas Cloudflare, Docker dan Nginx Proxy Manager sebagai sarana untuk meningkatkan keamanan web - Putra, Mochamad Yusuf Setiya; Affandi, Arif Saivul (Jurnal Ilmiah Teknologi Informasi Asia, 2025)
Cybersecurity is becoming an increasingly important matter as technology develops and threats against web-based applications grow. This research aims to examine how well Cloudflare, Docker, and Nginx Proxy Manager work, both alone and together, when used as an extra security measure to improve web application safety against these various threats. The study employed a quantitative approach using a quasi-experimental method with a posttest-only control group design. In this research, the control group consisted of a system without any additional security layers; this served as the starting point for measuring the system's security level. The experimental groups were divided into three types: a system using only Cloudflare, a system using only Docker and Nginx Proxy Manager, and a system using a combination of all three technologies. Testing involved several kinds of attacks, such as DDoS, brute force attacks, XSS, and SQL injections, utilizing tools like Slowhttptest, Burp Suite, XSSer, and SQL Map. The test results were assessed using descriptive analysis for categorical data and statistical methods for numerical data, specifically applying the One Way Anova or Kruskal Wallis tests, along with post-hoc follow-up tests. The findings from the study demonstrate that the system using the combination of Cloudflare, Docker, and Nginx Proxy Manager offered the most effective safety, reducing the number of successful attacks by up to 52% for DDoS, 69% for brute force attacks, 75% for XSS, and 100% for SQL injection. These results show a notable improvement compared to a standard system or systems using these security technologies individually.